Back to the heart. Collective creation of testimonial songs with incarcerated women in Mexico - Fernández de Juan, Teresa; Gomis Fernández, Leiden (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2024)
This article presents the project of collective creation of a testimonial song Volver al corazón, developed by one of the authors with 300 women deprived of their liberty, based on musical intervention strategies. It was carried out virtually (through the Zoom platform) during the COVID-19 pandemic simultaneously in five women’s prisons in Mexico: the Social Readaptation Center (Cereso) in Puentecillas, Guanajuato, the Nezahualcóyotl Bordo Penitentiary and Social Reinsertion Center in Xochiaca, the Tepozanes Women’s Prison and the “Santiaguito” Penitentiary and Social Reinsertion Center. all three in the State of Mexico, as well as the Women’s Social Reinsertion Center in Escobedo, Nuevo León. It was supported by socio-cultural animation tools, as well as the promotion of participation and collaborative action, with the purpose of linking the experiences of these women, getting them to recognize themselves. The contribution of Volver al corazón aims to link, through testimonial songs, the experiences of women deprived of their liberty. The result served not only as a testimony of the creative process, but also as a reference for public opinion and civil society, which will contribute to their social readaptation through a model that can be replicated at the national level.